2005
DOI: 10.2174/156802605774370856
|View full text |Cite
|
Sign up to set email alerts
|

Combining Cytotoxic and Immune-Mediated Gene Therapy to Treat Brain Tumors

Abstract: Glioblastoma (GBM) is a type of intracranial brain tumor, for which there is no cure. In spite of advances in surgery, chemotherapy and radiotherapy, patients die within a year of diagnosis. Therefore, there is a critical need to develop novel therapeutic approaches for this disease. Gene therapy, which is the use of genes or other nucleic acids as drugs, is a powerful new treatment strategy which can be developed to treat GBM. Several treatment modalities are amenable for gene therapy implementation, e.g. con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 212 publications
(182 reference statements)
1
34
0
Order By: Relevance
“…Importantly, recent experimental studies performed in mice have demonstrated that the stimulation of IS formation results in a potent tumor rejection involving GzmB polarization. 44 The demonstration here that CD8 ϩ T cells establish GzmB-mediated IS with tumorigenic cells in human GBM points the way toward strategies for tumor immunotherapy and identifies potential molecular targets, [45][46][47] which will permit the stimulation of CTL synapse formation.…”
Section: Org) Both Cd8mentioning
confidence: 87%
“…Importantly, recent experimental studies performed in mice have demonstrated that the stimulation of IS formation results in a potent tumor rejection involving GzmB polarization. 44 The demonstration here that CD8 ϩ T cells establish GzmB-mediated IS with tumorigenic cells in human GBM points the way toward strategies for tumor immunotherapy and identifies potential molecular targets, [45][46][47] which will permit the stimulation of CTL synapse formation.…”
Section: Org) Both Cd8mentioning
confidence: 87%
“…These immunotherapies are administered to cancer patients either alone or (most often) in combination with established therapeutic regimens. As outlined below and reviewed elsewhere (48), several promising gene therapy strategies have been developed in preclinical models to stimulate adaptive immune responses against tumors. However, tumors share many antigens with normal healthy tissue; therefore, a potential drawback with the use of immunotherapy is the development of autoimmunity (Fig.…”
Section: Is Regulation a Must For Genetherapy Applications?mentioning
confidence: 99%
“…Survival of patients affected by GBM has remained virtually unchanged during the past decades (6−12 mo after diagnosis) despite advances in surgery, radiation, and chemotherapy (8,12,16,24,27,37). Considering the poor prognosis of patients with high-grade glioma, novel therapeutic approaches are needed.…”
Section: Introductionmentioning
confidence: 99%